2023
DOI: 10.1002/cncr.34916
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after definitive radiation therapy for localized prostate cancer in a national health care delivery system

Abstract: PurposeAccurate information regarding real‐world outcomes after contemporary radiation therapy for localized prostate cancer is important for shared decision‐making. Clinically relevant end points at 10 years among men treated within a national health care delivery system were examined.MethodsNational administrative, cancer registry, and electronic health record data were used for patients undergoing definitive radiation therapy with or without concurrent androgen deprivation therapy within the Veterans Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Generally, radiation therapy is a safe and efficacious treatment option for men with localized prostate cancer. Herr et al found a 98%, 97% and 90% CSS, a 96%, 92%, and 80% MFS, and a 77%, 71%, and 62% OS, for low-, intermediate-, and high-risk prostate cancer at a median follow up of 8.7 years ( 18 ). A SEER database study by Guo et al found a cancer specific mortality rate of 2.3%, 2.0%, and 1.8% in heptogenarian patients with low- or intermediate-risk disease receiving external beam radiation therapy (EBRT), brachytherapy, or combination therapy, respectively ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, radiation therapy is a safe and efficacious treatment option for men with localized prostate cancer. Herr et al found a 98%, 97% and 90% CSS, a 96%, 92%, and 80% MFS, and a 77%, 71%, and 62% OS, for low-, intermediate-, and high-risk prostate cancer at a median follow up of 8.7 years ( 18 ). A SEER database study by Guo et al found a cancer specific mortality rate of 2.3%, 2.0%, and 1.8% in heptogenarian patients with low- or intermediate-risk disease receiving external beam radiation therapy (EBRT), brachytherapy, or combination therapy, respectively ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…93 % für ISUP 4 und 67 % bzw. 82 % für ISUP 5 [ 21 ]. In einer prospektiven Studie ( n = 347, 1989–1999) zur RP beim lokalisierten PCa lag die kumulative Inzidenz für Metastasen nach 23 Jahren bei 26,6 %.…”
Section: Diskussionunclassified